Lignin as Green Filler in Polymer Composites: Development Methods, Characteristics, and Potential Applications - Ridho, Muhammad Rasyidur; Agustiany, Erika Ayu; Rahmi Dn, Muslimatul; Madyaratri, Elvara Windra; Ghozali, Muhammad; Restu, Witta Kartika; Falah, Faizatul; Rahandi Lubis, Muhammad Adly; Syamani, Firda Aulya; Nurhamiyah, Yeyen; Hidayati, Sri; Sohail, Asma; et al. (Advances in materials science and engineering, 2022)
After cellulose, lignin is the most commonly used natural polymer in green biomaterials. Pulp and paper mills and emerging cellulosic biorefineries are the main sources of technical lignin. However, only 2–5% of lignin has been converted into biomaterials. Making lignin-based polymer biocomposites to replace petroleum-based composites has piqued the interest of many researchers worldwide due to the positive environmental impact of traditional composites over time. In composite development, lignin is being used as a filler in commercial polymers to improve biodegradability and possibly lower production costs. As a natural polymer, lignin may have different properties depending on the isolation method and source, affecting polymer-based composites. The application has been affected by the characteristics of lignin and the uniform distribution of lignin in polymers. The review’s goal was to provide an overview of technical lignin extraction, properties, and its potential appropriate utilization. It was also planned to revisit the lignin-based composites’ preparation procedure as well as their composite characteristics. Solvent casting and extrusion methods are used to fabricate lignin from polymeric matrices such as polypropylene, epoxy, polyvinyl alcohol, polylactic acid, starch, wood fiber, natural rubber, and chitosan. Packaging, biomedical materials, automotive, advanced biocomposites, flame retardant, and other applications for lignin-based composites has existed. As a result, the technology is still being refined to increase the performance of lignin-based biocomposites in several applications. This review could assist explain lignin’s position as a composite additive, which could lead to more efficient processing and application strategies.